Molecular biological and immunological techniques and applications for food chemists - Popping, Bert (Wiley, 2010)
A guide to using molecular biology and immunological methods for the analysis of food. Many of the analytical problems that food chemists face in the lab cannot be solved by chemistry alone, and so analytical chemists are turning to molecular biology and immunology for alternative approaches. Molecular Biological and Immunological Techniques and Applications for Food Chemists comprehensively explains the most important molecular biology and immunology methods, and illustrates their application in food analysis. Written by a distinguished group of experts, the coverage includes: Molecular Biolo.